Oil spill effects on macrofaunal communities and bioturbation of pristine marine sediments (Caleta Valdés, Patagonia, Argentina): experimental evidence of low resistance capacities of benthic systems without history of pollution - Ferrando, Agustina (2015)
The Patagonian coast is characterized by the existence of pristine ecosystems which may be particularly sensitive to oil contamination. In this study, a simulated oil spill at acute and chronic input levels was carried out to assess the effects of contamination on the macrobenthic community structure and the bioturbation activity of sediments sampled in Caleta Valdés creek. Superficial sediments were either noncontaminated or contaminated by Escalante crude oil and incubated in the laboratory for 30 days. Oil contamination induced adverse effects on macrobenthic community at both concentrations with, for the highest concentration, a marked decrease of approximately 40 and 55 % of density and specific richness, respectively. Besides the disappearance of sensitive species, some other species like Oligochaeta sp. 1, Paranebalia sp., and Ostracoda sp. 2 species have a higher resistance to oil contamination. Sediment reworking activity was also affected by oil addition. At the highest level of contamination, nearly no activity was observed due to the high mortality of macroorganisms. The results strongly suggest that an oil spill in this protected marine area with no previous history of contamination would have a deep impact on the non-adapted macrobenthic community.